2011
DOI: 10.12927/hcpol.2011.22178
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Healthcare Resources, Positive Ratings of the Care Experience and Extent of Service Use: An Unexpected Relationship

Abstract: Two main avenues are advocated to improve the capability of healthcare systems to satisfy the public' s needs and expectations: more resources and better organization. This paper sheds some light on this debate. It assesses the extent to which patients' positive rating of their healthcare experience and the extent to which they use services are related to the availability of healthcare resources. findings indicate that patients' evaluations of their care experience and use of services were higher when the avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
(1 reference statement)
1
10
0
Order By: Relevance
“…Second, according to our findings, integrating social participation practices is affected by enablers, mostly related to the therapists and emerging practices; systemic and organizational factors, such as performance indicators, institutional culture, and organizational pressure, restricted their integration. These findings are similar to those of other studies, where organizational factors were found to play an important role in the ability of health care services to meet population needs (Lamarche et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Second, according to our findings, integrating social participation practices is affected by enablers, mostly related to the therapists and emerging practices; systemic and organizational factors, such as performance indicators, institutional culture, and organizational pressure, restricted their integration. These findings are similar to those of other studies, where organizational factors were found to play an important role in the ability of health care services to meet population needs (Lamarche et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Systemic obstacles include the lack of funding for community services (Craig, 2012) as well as restrictive biomedical discourses on aging (Laliberte Rudman, 2005) that prevent occupational therapists from increasing older adults’ social participation (Trentham & Cockburn, 2011). Organizational factors, such as accessibility or continuity of services, further affect how health care services meet users’ needs, more so than the quantity or diversity of resources (Lamarche, Pineault, Gauthier, Hamel, & Haggerty, 2011). However, these factors may differ according to the service model used by community occupational therapists (Canadian Association of Occupational Therapists, 2016).…”
mentioning
confidence: 99%
“…Additionally, differences in availability, accessibility and affordability of healthcare services in home and host countries should be considered [56] . If immigrants are more likely to see a healthcare professional in a host country than in their home country due to available infrastructure and low cost services at accessible locations, then this is crucial for the likelihood of being diagnosed with either asthma or allergies preceding migration (particularly so for migrants from developing home and developed host countries), and this could somewhat affect the prevalences observed in this review.…”
Section: Discussionmentioning
confidence: 99%
“…The results reflect how these issues were perceived and experienced by the 13 participants who took part in two focus group sessions, and may not reflect all issues related to QoC in the physiotherapy domain for CSST patients. Another limitation is that all participants worked in an urban region (greater Montreal) and the results may be less applicable to care in rural regions (Lamarche et al 2011). Finally, the participants are themselves interested by the CSST system, and their insights might not reflect the variety of perspectives among PTs and PRTs Anne Hudon et al who treat injured workers.…”
Section: Limitationsmentioning
confidence: 99%